Household glassware products obtained from cullet and method for producing the same
By using a mixture of high content of broken glass and ZnO to produce household glassware products, the problems of insufficient durability and high energy consumption in the prior art are solved, and high durability and environmentally friendly glass products are achieved.
Patent Information
- Application Number
- CN202180054711.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-08
- Filing Date
- 2021-03-24
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-03-24
AI Technical Summary
Existing household glassware products are not durable in dishwashers, and have high energy consumption during production, and have a high risk of pollution.
The production of household glassware products is made of a mixture of at least 95% broken glass and up to 5% ZnO, improving the chemical durability of glass and dishwasher durability by optimizing process conditions and adding oxides such as ZnO.
It significantly improves the durability of glassware products in dishwashers and atmospheric corrosion durability, reduces the risk of energy consumption and pollution, and the glass produced is almost colorless.
Smart Images

Figure CN116323505B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a household glassware product with high chemical corrosion durability and a production method thereof. Background Art
[0002] In domestic glassware, glass is produced from raw glass and its internal cullet in a low ratio (15-40%) from a mixture.
[0003] In glass production, the desired impurities and color parameters in the glass are very important. By adjusting the mixture content and the use of internal cullet, the desired color, mechanical properties and durability of the glass in the dishwasher can be controlled. The content of the raw materials, especially the amount of Fe2O3 as an impurity, has an impact on the color parameters of the glass. A high content of Fe2O3 from the raw materials increases the need to reduce the glass brightness value and the decolorization mechanism. During the melting of standard soda-lime glass mixtures, the energy required for the reaction is higher than the energy required for the melting of the glass cullets. In addition to this, only internal cullets are used in the production of household glassware products to keep the risk of contamination at a low level to prevent or control the presence of undesirable elements in the glass composition. In glass production, the energy required between the melting of the mixture and the melting of the cullet is also different. As is known in the art, a 10% increase in the use of cullet can save about 2% of the energy required for melting. The purpose is to reduce the energy demand in glass production and thus reduce production emissions.
[0004] The use of cullet in domestic glassware production is limited to its internal circulation, so the amount of cullet produced cannot exceed 40% depending on the type of production (blown, capped, pressed, etc.). At the same time, the colorlessness of the glass obtained by recycling glass using existing technologies is very low.
[0005] In the patent document of publication number WO9931022A1, the production of recyclable colored glass is mentioned. In particular, it relates to amber glass, which is obtained by mixing mixed colored cullet containing green, amber and colorless glass by adding iron, carbon, sulfur and sulfur compounds to the mixture to obtain the desired red color. The invention is used to produce recycled green or flint glass from undecomposed mixed colored cullet. The invention is particularly suitable for producing amber containers or beverage bottles for beverages that need to be protected from light damage, such as beer. Summary of the invention
[0006] The present application relates to household glassware product glass, which is made of cullet and has high durability in a dishwasher, thereby bringing new advantages to the above-mentioned related technical field.
[0007] The main object of the present application is to provide a glass obtained using ≥ 95% of cullet.
[0008] Another object of the present application is to provide a glass obtained using ≥ 95% of cullet.
[0009] Another object of the present application is to provide a nearly colorless glass and household glassware product.
[0010] Another object of the present application is to provide a household glassware glass which has a high durability in a dishwasher.
[0011] Another object of the present application is to make glass production more environmentally friendly.
[0012] Another object of the present application is to provide a glass and domestic glassware article in which atmospheric corrosion durability is increased.
[0013] The present application relates to a household glassware product made from soda-lime-silica cullet to achieve all the above objects and as will appear from the detailed description below. It therefore contains at least 95% by weight of cullet selected from recycled, internal cullet or mixtures thereof and at most 5% ZnO. As a result, the durability of the dishwasher is improved.
[0014] In a preferred embodiment of the present application, the weight ratio of components of the cullet composition is as follows.
[0015]
[0016]
[0017] Another preferred embodiment of the present application is that the glass contains oxides CeO2, CoO, SeO and Er as colorants, decolorants and / or oxidants. x O y The total amount of at least one oxide does not exceed 0.5 wt%.
[0018] Another preferred embodiment of the present application is that the Lab color parameter L* value of the glass with a thickness of 10 mm is between 83 and 89, the a* value is between -4 and 0, and the b* value is between -0.5 and 1.5.
[0019] Another preferred embodiment of the present application is that the direct thermal expansion value is 85×10 -7 / ℃ to 89×10 -7 / ℃.
[0020] Another preferred embodiment of the present application is that the refractive index is between 1.51 and 1.52.
[0021] Another preferred embodiment of the present application is that the glass does not corrode during measurements performed according to the EN 12875 standard.
[0022] The present application is a process for producing household glassware articles made from soda-lime-silica cullet, to achieve all the above objects, as will appear from the detailed description below. It is therefore produced with a mixture of at least 95% cullet and at most 5% ZnO. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] exist Figure 1 Surface SEM images of samples belonging to the present SLS composition at the end of 200 washing cycles are shown in FIG. DETAILED DESCRIPTION
[0024] In this specific embodiment, in order to better understand the present application, examples are used to explain the household glassware products and production methods of the present application, and the examples do not have any limiting effect.
[0025] Herein, "%" means "% by weight" of the content and amount of a specific substance unless otherwise specified.
[0026] In this study, soda-lime-silica cullet was used, the composition ratio of which is shown in Table 1. At least 95% of soda-lime cullet and a maximum of 5% of ZnO were fed into the furnace. The ZnO ratio used in the examples of this application was between 1-2%. As a source of cullet, recycled 1. cullet generated during the production process (internal cullet), 2. a combination of these were used.
[0027] To achieve the desired melting and refining, cullet and / or other raw materials are melted by optimizing process conditions and heating to high temperatures. The composition of cullet, which constitutes 95% of the glass, is shown in Table 1.
[0028] Table 1: Cullet composition
[0029] Element weight% <![CDATA[SiO2]]> 69-73 <![CDATA[Al2O3]]> 1-2 <![CDATA[Fe2O3]]> 0.01-0.1 CaO 8-11 MgO 1-4 <![CDATA[Na2O]]> 12-15 <![CDATA[K2O]]> 0-1 <![CDATA[SO3]]> 0-0,3
[0030] In a preferred embodiment of the present application, the cullet composition comprises 69-71 wt. % SiO2, Al2O3 in the range of 1-2%, Fe2O3 in the range of 0.01-0.10%, CaO in the range of 8-9%, MgO in the range of 1-3%, Na2O in the range of 12-14% and K2O in the range of 0-1%.
[0031] Domestic glassware products containing at least 95% cullet can be made colored or flint. The cullet compositions given above can contain oxides CeO2, CoO, SeO and Er as colorants, decolorants and / or oxidants. x O y At least one of the above, the total amount of which does not exceed 0.5%.
[0032] The glass production using cullet of the present application is suitable for glass packaging, household glassware products and flat glass applications.
[0033] In the case of flint, a glass with a thickness of 10 mm, obtained from cullet with a given content, has an L* value between 83 and 89, an a* value between -4 and 0, and a b* value between -0.5 and 1.5 in Lab color parameters. In a preferred embodiment, a glass with a thickness of 10 mm obtained from cullet has an L* value between 84 and 88, an a* value between -3 and -1, and a b* value between 0 and 1 in Lab color parameters. In an alternative embodiment, a glass with a thickness of 10 mm obtained from cullet has an L* value between 85 and 87, an a value between -2 and -1, and a b value between 0.5 and 1.5 in Lab color parameters.
[0034] Although a mixture of recycled and internal cullet is mostly used, if the color parameters of the final glass product are expected to be the same or close to those of colorless glass, the proportion of internal glass cullet used is increased. Thus, impurities from the outside can be more effectively controlled.
[0035] The production of colored domestic glassware products can be carried out using colorants of the desired hue.
[0036] The glass obtained from soda-lime glass production is prepared for forming in the forehearth. The direct thermal expansion value of the formed household glassware products is 85×10 -7 / ℃~89×10 -7 / ℃. The refractive index measurement value is between 1.51-1.52.
[0037] In the present application, in order to improve the washing durability of articles produced using at least 95% soda-lime-silica cullet, ZnO is added in a proportion of 0-5%. This makes the glassware articles less susceptible to atmospheric corrosion and can withstand washing cycles in dishwashers.
[0038] The temperature distribution in the dishwasher depends on several parameters, such as the duration and number of wash cycles, the pH value and pH changes during the wash cycle, the water hardness, composition and concentration of the detergent used. In addition, the composition of the glass, the secondary treatment of the surface and the storage conditions (atmospheric conditions: humidity, temperature, etc.) also have an influence on the corrosion of the glass.
[0039] In an environment containing moisture and water vapor, changes in surface morphology and / or composition can occur with various reactions occurring on the glass surface. Reactions that may occur here take the form of ion replacement and / or weakening and breaking of Si-O bonds.
[0040] Washing in a dishwasher or in an environment containing moisture / water vapor will accelerate changes on the glass surface that, while they may not be visible at first, may become noticeable over time.
[0041] The effect of the metal oxides forming the glass composition on chemical durability occurs through three different mechanisms:
[0042] 1. The lower the hydration temperature of the metal oxides in the glass, the higher the chemical durability of the glass. The hydration temperature decreases according to the following metal oxide arrangement: K2O, Na2O, BaO, SrO, CaO, MgO, B2O3, ZnO. Therefore, ZnO provides the highest chemical durability, especially to water vapor.
[0043] 2. The type of bond (ionic or covalent) varies depending on the electronegativity of the atoms forming the bond or their atomic diameters. Polarization occurs when the electrons in the bond are unequally shared by the atoms. High charge density in cations and large anions affect polarization. Elements that tend to be highly polarized have low melting points. Therefore, they reduce the viscosity and surface tension of the glass melt and tend to volatilize the glass melt. At the same time, they reduce the chemical durability of the glass surface.
[0044] In this case, the higher the atomic refractive index (ability of bonded atoms to polarize), the higher the chemical durability of the undisturbed glass surface and the volatility of the oxide. In the glass production process, oxides formed by cations with a high atomic refractive index are more easily separated from the glass surface. This results in a surface rich in silicon dioxide for household glassware products. In this embodiment, an atomic refractive index of 16 or higher is considered high. For example, this is the case for Ba, Pb, Ti and Zr. The atomic refractive index of the elements Mg, Al, Si, K, Zn, Ca increases from 6 to 10, respectively.
[0045] 3. Chemical durability depends on the degree of ionization in the glass (the ratio of the number of ionic bonds to the number of covalent bonds between MO bonds in the structure). The atoms in the glass structure form ionic or covalent bonds, and high ionization corresponds to lower chemical durability. Among the oxide bonds in the glass, KO, Na-O, Ba-O and Ca-O have a higher degree of ionization (1-2.5), Al-O and Zn-O have a degree of ionization of 1, and Si-O and BO have a lower degree of ionization (0.7-0.5).
[0046] According to the information given here, in order to make the glass composition have higher durability in the dishwasher than the basic alkaline soda-lime glass, ZnO, water and water vapor are used, thus it provides the glass with high chemical durability for applications requiring high temperatures, such as sterilization and washing in the dishwasher.
[0047] The durability of newly produced samples belonging to the composition test in the dishwasher was checked for 500 cycles within the framework of the "EN 12875 / 1" standard. Mechanical durability of utensils - Part 1: Reference test method for household articles.
[0048] The washing cycle conditions are as follows:
[0049] Cold pre-wash (5 minutes, 20°C, 6±0.5L water)
[0050] Main wash with detergent (30 minutes, 60℃, 6±0.5L water)
[0051] Rinse (3 minutes, 20°C, 6±0.5L water)
[0052] Rinse aid + final rinse (20 minutes, 65°C, 6±0.5L water)
[0053] Drying (10 minutes with door closed, 30 minutes with door open)
[0054] Water hardness: 0.3-0.6mmol / L
[0055] Detergent: Powder, Type C* (24±3g)
[0056] Rinse aid: 2.5-3.0g
[0057] According to the standard "EN 12875 / 2", at the end of every 10 washing cycles, the household glassware articles of the present application, containing at least 95% of broken glass and a maximum of 5% of ZnO content, are evaluated based on clouding and tempering over the entire surface. Mechanical washability of glassware - Part 2: Test of non-metallic articles. The standard numbered EN 12875 / 2 is shown below.
[0058] Observation results ranking
[0059] 0No change
[0060] 1The first obvious change
[0061] 2 Visible changes
[0062] The test results are shown in Table 2. There is no difference in dishwasher washing durability between the newly prepared samples of the soda-lime-silica (hereinafter referred to as SLS) composition of the present application and the ZnO-containing composition.
[0063] Table 2: Test results of newly produced test samples of compositions according to standard EN 12875 / 1
[0064] Composition Molding type, mold number 500 cycles 1% ZnO Suppression 52052 0 1% ZnO Press Blow 42405 0 0.5% ZnO Suppression 52052 0 0.5% ZnO Press Blow 42405 0 SLS Suppression 52052 0 SLS Press Blow 42405 0
[0065] EN 12875 / 4 Durability of household items for washing in dishwashers in the rapid method
[0066] Within the framework of the standard "EN 12875 / 4, Mechanical durability of tableware - Part 4: Rapid tests for domestic ceramics", the durability of newly produced samples belonging to the composition test in the dishwasher was checked. The samples were immersed in a 0.5% (w / w) detergent solution at a temperature of 75°C for a total of 64 hours (according to EN 12875 / 1 6 , equivalent to 500 cycles). According to the standard "EN 12875 / 2, Mechanical durability of tableware - Part 2: Test of non-metallic products", the samples were evaluated every 16 hours, evaluating shadows and wear over the entire surface. The test results are shown in Table 3 below. There are no obvious differences between the compositions visible to the naked eye.
[0067] Table 3: Test results of newly produced test samples of compositions according to standard EN 12875 / 4
[0068] Composition Molding type, mold number 64 hours 1% ZnO Suppression 52052 0 1% ZnO Press Blow 42405 0 0.5% ZnO Suppression 52052 0 0.5% ZnO Press Blow 42405 0 SLS Suppression 52052 0 SLS Press Blow 42405 0
[0069] Atmospheric corrosion (aging) inspection
[0070] The developed samples improve the durability of the SLS glass compositions produced automatically to atmospheric corrosion, and thus dishwasher durability is obtained by adding ZnO to the compositions in Table 1. The atmospheric corrosion durability of the trial samples was compared with the atmospheric corrosion durability of the present SLS compositions. For this purpose, all samples were first placed in a conditioning cabinet for a period of time to subject them to atmospheric corrosion (aging), and then subjected to washing tests.
[0071] Atmospheric corrosion test of test samples of the composition
[0072] Freshly produced test samples of the composition were aged in a conditioning cabinet. To this end, the samples were exposed to the following environmental conditions, which were varied every 12 hours:
[0073] 12 hours at 95% RH, 50°C
[0074] 12 hours indoor conditions.
[0075] 10 days non-stop. The surface of the aged samples was inspected before washing. No visible corrosion was detected on the sample surface.
[0076] Washing test of aged composition test samples
[0077] Within the framework of the standard "EN 12875 / 1, Mechanical washability of tableware - Part 1: Reference test methods for household articles", the durability of test specimens of the composition aged in a conditioning cabinet was checked for 500 cycles in a dishwasher. According to the standard "EN 12875 / 2, Mechanical washability of tableware - Part 2: Test of non-metallic articles", at the end of each 10 washing cycles, the specimens were evaluated for shading and wear of the entire surface. The test results are shown in Table 4.
[0078] After 500 cycles, no corrosion was observed on the surface of the aged samples tested with the 1% and 0.5% ZnO compositions. The surface of the aged sample of the SLS composition sample showed shadows after 200 cycles. The surface of the sample with shadows was examined by SEM-EDS, and the images are shown in Fig. Figure 1 As shown in Figure 2, Si depletion was observed on the sample surface.
[0079] Table 4: Test results of aged samples according to standard EN 12875 / 1
[0080] Composition Molding type, mold number 200 cycles 500 cycles 1% ZnO Suppression 52052 0 0 1% ZnO Press Blow 42405 0 0 0.5% ZnO Suppression 52052 0 0 0.5% ZnO Press Blow 42405 0 0 SLS Suppression 52052 shadow shadow SLS Press Blow 42405 shadow shadow
[0081] Glass composition research results
[0082] Within the framework of the standard "EN 12875 / 1, Mechanical washability of tableware - Part 1: Reference test methods for household articles, Part 2: Examination of non-metallic articles", the durability of newly produced and aged samples of compositions was tested for 500 cycles to improve the durability of glass compositions against atmospheric corrosion and thus dishwasher durability (in terms of shadowing and abrasion of the entire surface). No differences were observed between the test samples of the newly produced compositions. After 500 cycles, no corrosion was observed on the sample surface.
[0083] 1. No corrosion was observed on the aged sample surface of the 1% and 0.5% ZnO composition test after 500 cycles. The aged sample of the SLS composition sample had a shadowy surface after 200 cycles.
[0084] These results indicate that ZnO improves the atmospheric durability of the soda-lime-silicate glass composition, thereby improving the durability of the article in a dishwasher.
[0085] Glass composition:
[0086] The research aimed to improve the chemical durability of SLS glass compositions, thus improving their resistance to atmospheric corrosion and dishwasher cleaning (in terms of shadowing and abrasion of the entire surface). In this regard, 3 different compositions were produced:
[0087] 1% ZnO (1% ZnO added by reduction from SiO2),
[0088] 0.5% ZnO (0.5% ZnO added by reduction from SiO2),
[0089] Current SLS composition,
[0090] Dishwasher durability:
[0091] - Newly produced and
[0092] -Aging,
[0093] Samples of these compositions were tested for shadows and abrasion over the entire surface after 500 cycles according to the standard "EN 12875 / 1, Mechanical durability of utensils - Part 1: Reference test methods for household articles". The results obtained are as follows:
[0094] 1. No differences were observed between the test samples of the newly produced compositions.
[0095] 2. No corrosion was observed on the surface of the aged samples tested with the 1% and 0.5% ZnO compositions after 500 cycles. The aged samples of the current SLS composition showed shadowing on the surface after 200 cycles.
[0096] These results indicate that ZnO improves the atmospheric durability of soda-lime-silicate glass compositions, thereby improving the durability of the product in dishwashers.
[0097] The protection scope of the present application is defined in the attached claims, and it is not limited to what is explained in this detailed description for the sake of example.Obviously, those skilled in the art can provide similar embodiments according to the above content without departing from the subject matter of the present application.
Claims
1. A glass made from soda-lime-silica cullet, characterized in that: The glass contains at least 95% by weight of cullet selected from recycled cullet and at most 5% of ZnO; The weight ratio of the components of the cullet composition is as follows: 。 2. The glass according to claim 1, characterized in that The glass contains oxides CeO2, CoO, SeO and Er as colorants, decolorants and / or oxidants. x O y The total amount of the oxides does not exceed 0.5 wt %.
3. The glass according to claim 1, characterized in that The Lab color parameter L* value of glass with a thickness of 10 mm is between 83 and 89, the a* value is between -4 and 0, and the b* value is between -0.5 and 1.
5.
4. The glass according to claim 1, characterized in that The thermal expansion coefficient of the glass is 85×10 -7 / ℃ to 89×10 -7 / ℃.
5. The glass according to claim 1, characterized in that The refractive index is between 1.51 and 1.
52.
6. The glass according to claim 1, characterized in that The glass does not corrode in measurements carried out in accordance with standard EN 12875.
7. A method for producing the glass according to claim 1, characterized in that: The glass is produced from a mixture of at least 95% cullet and at most 5% ZnO.
8. Use of the glass according to claim 1 in glass packaging, household glass products and flat glass.
Citation Information
Patent Citations
A method of recycling mixed colored cullet into amber, green, of flint glass
WO1999031022A1
Soda-lime silicate plate-like glass and manufacturing method thereof
CN101353225A
Crystal glass article
CN101356127A
Method for producing bleached foam glass
JP2019059629A